Multihoming based mobility management scheme in NEMO: a qualitative and quantitative analysis - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Abdul Latif, Suhaimi; Hasan, Mohammad Kamrul; A. Saeed, Rashid (2013)
In order to support mobile network, a management mechanism of Network Mobility Basic Support Protocol (NEMO BSP) has been standardized by Information Engineering Task Force (IETF). NEMO BSP is an extension of Mobile IPv6 (MIPv6) and inherits all the shortcomings like higher handoff latency, packet loss etc. As Network Mobility (NEMO) is engaged to manage the movement of Mobile Router (MR) and it's Mobile Network Nodes (MNNs) during handoff, it is very important to improve the performance of mobility management protocol to achieve continuous Internet connectivity with lower delay and packet loss in NEMO environment. When a change in point of attachment of the mobile network is accompanied by a sudden burst of signaling messages, "Signaling Storm" occurs and it ultimately results in temporary congestion, handoff delays, or even packet loss. This effect is especially noteworthy for wireless environment where bandwidth is relatively limited. Therefore providing uninterrupted Internet connection through applying multihoming technique in NEMO is becoming most significant areas for current researchers. The purpose of this paper is to give a general overview on existing mobility management approaches which enable multihoming and network based mobility protocol with NEMO in an integrated manner. Furthermore, it highlights the strengths and the limitations of these schemes for future analysis.